The clinical features and prognosis of COVID-19 in diabetic patients - Behera, Ashok Kumar; Chhotaray, Saubhagya; Beshra, Sabitri; Marndi, Chhatray; Patra, Gopabandhu (International Journal of Research in Medical Sciences, 2023)
Background: It is well-recognized that uncontrolled glycemia reflects the severity and mortality rates of respiratory virus epidemics. The aim of the study was to report the features and course of therapy of diabetic individuals admitted to a tertiary care facility with COVID-19 infection. Additionally, we tried to assess how hyperglycemia affected the clinical results. Methods: This study used observational methods to conduct a retrospective chart review of 125 cases from October 2021 to March 2022 at a single center. Results: Males made up 94.6% of the 125 examined cases. Within the age range of 21 to 78 years, the study group's average age was 49.6±10.4 years. Of the patients, 66.4% had prior knowledge of diabetes. When compared to pre-existing diabetes individuals with the newly diagnosed diabetes individuals, the latter had a higher death rate (p=0.03) and needed mechanical breathing (p=0.02). Conclusions: Hyperglycemia that is uncontrolled harms COVID-19-infected patients. There is an increased risk of hyperglycemia problems that have been discovered or unknown.to screen for cases of undiscovered diabetes in hospital patients, which may be especially relevant during the COVID-19 pandemic, optimal glycemia optimization is essential.